Effect of silver nanoparticles on Candida albicans biofilms: an ultrastructural study. Issue 1 (December 2015) - Lara, Humberto; Romero-Urbina, Dulce; Pierce, Christopher; Lopez-Ribot, Jose; Arellano-Jiménez, M.; Jose-Yacaman, Miguel
Abstract Background Candida albicans is the most common pathogenic fungus isolated in bloodstream infections in hospitalized patients, and candidiasis represents the fourth most common infection in United States hospitals, mostly due to the increasing numbers of immune- and medically-compromised patients.C. albicans has the ability to form biofilms and morphogenetic conversions between yeast and hyphal morphologies contribute to biofilm development and represent an essential virulence factor. Moreover, these attached communities of cells are surrounded by a protective exopolymeric matrix that effectively sheltersCandida against the action of antifungals. Because of dismal outcomes, novel antifungal strategies, and in particular those targeting biofilms are urgently required. As fungi are eukaryotic, research and development of new antifungal agents has been difficult due to the limited number of selective targets, also leading to toxicity. Results By microwave-assisted techniques we obtained pure 1 nm spherical silver nanoparticles ideal for their potential biological applications without adding contaminants. A phenotypic assay ofC. albicans demonstrated a potent dose-dependent inhibitory effect of silver nanoparticles on biofilm formation, with an IC50 of 0.089 ppm. Also silver nanoparticles demonstrated efficacy when tested against pre-formedC. albicans biofilms resulting in an IC50 of 0.48 ppm. The cytotoxicity assay resulted in a CC50 of 7.03 ppm. The ultrastructural differences visualized under SEM with silver nanoparticles treatment were changes in the surface appearance of the yeast from smooth to rough thus indicating outer cell wall damage. On the fungal pre-formed biofilm true hyphae was mostly absent, as filamentation was inhibited. TEM measurement of the cell-wall width ofC. albicans after treatment resulted in significant enlargement (206  ±  11 nm) demonstrating membrane permeabilization. Conclusions Our results demonstrate that silver nanoparticles are potent inhibitors ofC. albicans biofilm formation. SEM observations are consistent with an overall loss of structure of biofilms mostly due to disruption of the outer cell membrane/wall and inhibition of filamentation.TEM indicates the permeabilization of the cell wall and subsequent disruption of the structural layers of the outer fungal cell wall. The anti-biofilm effects are via cell wall disruption.